The democracy polish in the traffic mirror - Moraes, João Quartim de (2009)
This paper tries to analyze the concrete and ideological meaning of the so many times observed atrophy of the meaning of civility, of citizenship and of public space in the Brazilian society, as it is clearly seen in the traffic in everyday life.